Mental health and quality of life of female breast cancer survivors in Southeast Serbia - Žikić, Olivera; Cvetanović, Ana; Kostić, Jelena; Nikolić, Gordana; Stojanov, Jelena; Binić, Iva (Vojnosanitetski pregled, 2024)
Background/Aim. Quality of life (QoL) is one of the outcome measures for patients with chronic diseases. Mental health issues often impact the QoL of cancer patients. Cancer patients with a good QoL have a longer life expectancy and are able to lead a more productive and social life. The aim of the study was to determine the association of mental health with the QoL, as well as to determine significant predictors of QoL in patients with breast cancer (BC). Methods. The study included 118 patients treated at the Specialized Breast Cancer Department of the Oncology Clinic of the University Clinical Center Niš, Serbia. The study’s inclusion criteria were the presence of early-stage nonmetastatic BC and completed surgical treatment. The following questionnaires were used: the general sociodemographic questionnaire, Hospital Anxiety and Depression Scale (HADS), Buss-Perry Aggression Questionnaire, Early Maladaptive Schema questionnaire - short form (SQ-SF), Flanagan’s Quality of Life Scale (QoLS), Holmes and Rahe Stress Scale, Berlin Social Support Scales (BSSS), Health Locus of Control. Results. A statistically significant negative correlation was found with emotional state, i.e., anxiety score, depressiveness score, total stress score, and physical aggression score, while QoL correlated positively with all subscales of the perceived social support (PSS) questionnaire. QoL was significantly different for patients with the following early maladaptive schemas: emotional deprivation, emotional inhibition, and a sense of entitlement/narcissism. Moreover, QoL differed significantly depending on partnership status, the presence of clinically significant anxiety, the presence of hormone-sensitive cancer, the presence of human epidermal growth factor receptor 2 (HER2)-positive cancer, and time since diagnosis. Multiple linear regression was performed, and depression and PSS had the highest share. Conclusion. In our study, the presence of depressiveness and PSS were the best predictors of QoL of BC survivors.
Keywords: breast neoplasms; emotions; mental health; prognosis; quality of life; social factors; surveys and questionnaires; women.